2020
DOI: 10.1002/jcop.22458
|View full text |Cite
|
Sign up to set email alerts
|

Change in housing environment and residential satisfaction following exit from permanent supportive housing

Abstract: Moving On initiatives (MOIs) transition stable permanent supportive housing (PSH) residents into mainstream housing without embedded services. While this approach frees up PSH for homeless individuals in need, open questions remain regarding MOI recipients' long-term outcomes. This exploratory study examines how housing environment and residential satisfaction, potential predictors of housing retention, change from PSH to mainstream housing. Subjective assessments of housing and neighborhood quality and reside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Suggested strategies from MOI implementers include the use of landlord incentives, letters of support for MOI recipients’ housing applications and establishing relationships with housing gatekeepers (e.g. landlords and brokers) to break down misperceptions about movers (Tiderington et al ., 2020a, Tiderington et al ., 2020b, Gurdak et al ., 2020). This study also highlights, through the eyes of PSH residents, some of the secure benefits of living in this setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Suggested strategies from MOI implementers include the use of landlord incentives, letters of support for MOI recipients’ housing applications and establishing relationships with housing gatekeepers (e.g. landlords and brokers) to break down misperceptions about movers (Tiderington et al ., 2020a, Tiderington et al ., 2020b, Gurdak et al ., 2020). This study also highlights, through the eyes of PSH residents, some of the secure benefits of living in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that PSH improves housing stability, community integration and psychological well-being for people with histories of homelessness (Culhane et al , 2002; Gulcur et al , 2007; Padgett et al , 2016; Pearson et al , 2009; Stefancic and Tsemberis, 2007; Tsemberis et al , 2012; Yanos et al , 2007). However, participants who have left PSH through MOIs have reported improved psychological well-being, housing retention and increased housing satisfaction post-PSH exit (Feiss et al , 2019; Perez et al , 2019; Tiderington, 2020, Tiderington et al ., 2020a, Tiderington et al ., 2020b, Gurdak et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies have assessed PSH outcomes within a 2-year follow-up period, or less [16,20]. Satisfaction with services, a key factor contributing to service retention and to recovery, was included in this study [21]. This variable was measured based on a question with a 5-point score (1=very unsatisfied to 5=very satisfied).…”
Section: Variables and Instrumentsmentioning
confidence: 99%
“…There are PSH programs throughout the country, however, many programs operate in scarcity—meaning they operate in a context characterized by a lack of housing subsidies, housing inventory, and/or staffing (Austin et al, 2014; Ridgway & Zipple, 1990; Stefancic & Tsemberis, 2007). Thus, there is a need for communities to prioritize PSH services and develop procedures to ensure that once housed, PSH residents are able to maintain their tenancies or transition to other permanent housing situations as appropriate (Tiderington et al, 2021; Toros & Flaming, 2018).…”
mentioning
confidence: 99%